Taxation and economic development in India - Cutt, James (New York ; London : Praeger, 1969)
This book is on the Indian constitution that provide division of tax between powers and the union
Based on the author's thesis, University of Toronto, 1966.
Includes bibliographical references: p. 395-413.
oo 30/08/2018
Loans
Keywords: Taxation